Postawa Henryka IX Głogowskiego i Jana Żagańskiego wobec wypraw husyckich w roku 1432 w świetle listów wójta nowomarchijskiego do wielkiego mistrza zakonu krzyżackiego = Henryk IX Głogowski and Jan Żagański and the hussite incursions of 1432 - as described by the governor of Neumark in his letters to the grand master of the teutonic knights - Karp, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the history of the Hussite movement, the year 1432 stands out because of the significant military and diplomatic successes. The Bohemians ventured then abroad (so-called 'beautiful raids'). In March, having crossed Silesia and Lusatia, they invaded Barandenburg and got as far as Berlin. In order to save their lands from the ravages of the war, Frederick I, Margrave of Brandenburg, Elector of Saxony, and numerous Silesian dukes and noblemen of the Jauer-Schweidnitz and the Breslau duchies were forced to agree on a truce with the Hussiteleaders.
Keywords: Henryk IX Starszy (głogowski) (książę; między 1387 a 1392-1467); Jan I żagański (książę; ok. 1385-1439); husyci; Śląsk, Dolny - historia; Księstwo Głogowskie - historia; epistolografia; 15 w.